1987
DOI: 10.1111/j.1471-4159.1987.tb02434.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Expression of Gangliosides During Differentiation of Chick Embryo Retina Cells In Vitro

Abstract: Cells from neural retina from 7-day chick embryos were cultured on polylysine-coated dishes up to 7 days. The small, round-shaped cells at seeding differentiated progressively, and after 4 days in vitro the majority had enlarged bodies and abundant processes. The content of protein and DNA was essentially unchanged during the entire period of culture. The incorporation of radioactivity from [3H]glucosamine into gangliosides declined slightly, reaching about 65% of the initial values at the end of the culture p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 48 publications
5
33
1
Order By: Relevance
“…In embryonic rat brain, major GD 3 synthase activity has been observed during early embryonic stages, while an increase in GM 2 synthase activity has been shown to occur during later embryogenesis and adulthood (6,7). Similar results have been observed in embryonic chick retina and embryonic human brain (5,8).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In embryonic rat brain, major GD 3 synthase activity has been observed during early embryonic stages, while an increase in GM 2 synthase activity has been shown to occur during later embryogenesis and adulthood (6,7). Similar results have been observed in embryonic chick retina and embryonic human brain (5,8).…”
Section: Resultssupporting
confidence: 61%
“…Modifications in the ganglioside pattern during development may be associated with correspoding changes in the activities of specific glycosyltransferases. In the chick embryo retina system and the mammalian brain developmental changes in ganglioside composition correlate with variations in the activities of the key ganglioside glycosyltransferases: GD 3 and GM 2 synthases (5)(6)(7)(8). Gamallo and Bernard (9) demonstrated that rat testes gangliosides show a pattern of increasing complexity with aging.…”
mentioning
confidence: 98%
“…This ratio was substantially higher than that reported by Quiroga et al (1990). It might be noted that in the present experiment the labeled glucosamine was added at the second day in vitro, and in the experiment by Quiroga et al it was at the fourth day, and in that period a dramatic change in the relationship between GD3 and GDla synthesis occurs in normal cells: the GD3 synthesis decays fivefold and that of GDla increases twofold (Panzetta et al, 1987).…”
Section: Removal Of the Inhibitorcontrasting
confidence: 74%
“…From our data and data taken from other authors (see Table II), we calculated that the pathway "a" to pathway "b" ganglioside ratio was lower in mammalian retina than in chick retina and chick, rat, and human brain. We have already suggested (Panzetta et al, 1987;Maccioni et al, 1989) that the high proportion of pathway "a" gangliosides in the adult chick retina was probably due to the low activity of GD3 synthetase coexisting with high activities of the GM2 and GMl synthetases, which lead to the conversion of GM3 into gangliosides of the gangliotetraosylceramide series. We would predict that the balance of GD3iGM2 (and GM 1) synthetase activities would favor CD3 synthetase in the mammalian retinas, although this issue must be further investigated.…”
Section: Discussionmentioning
confidence: 92%